2021
DOI: 10.1039/d0cs01605e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in electrocatalysis with phthalocyanines

Abstract: This review provides a timely and comprehensive overview of the recent progresses in the synthesis and application of phthalocyanine-based heterogeneous electrocatalysts, as well as the structure/composition–catalytic activity relationship, and future prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
123
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(141 citation statements)
references
References 209 publications
0
123
0
Order By: Relevance
“…The high electrocatalytic and photocatalytic activities of MPcs can be attributed to the unsaturated low-coordination environment of the central metal ions coordinated to four isoindole subunits. 15 Current researches focus on the physical and chemical properties of metal phthalocyanines with side chains under non-photoexcited conditions. Although it has been shown that the central metal in MPcs played an important role in various photocatalytic and electrocatalytic reactions, the precise control by light or solvent effects is required to develop a deeper understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The high electrocatalytic and photocatalytic activities of MPcs can be attributed to the unsaturated low-coordination environment of the central metal ions coordinated to four isoindole subunits. 15 Current researches focus on the physical and chemical properties of metal phthalocyanines with side chains under non-photoexcited conditions. Although it has been shown that the central metal in MPcs played an important role in various photocatalytic and electrocatalytic reactions, the precise control by light or solvent effects is required to develop a deeper understanding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cobalt porphyrin, cobalt phthalocyanine, which also has CoN 4 active sites, is also an effective molecular catalyst for CO 2 RR. 552,553 Since 2020, several examples of 2D cobalt phthalocyanine-COFs for CO 2 RR have been reported. 147,212,216,220 In these COFs, the metallophthalocyanines are connected by strong covalent bonds, including phenazine, imide, and dioxin linkages, to form robust planar sql lattices.…”
Section: Application Of Metalated Cofsmentioning
confidence: 99%
“…It is known that MPc sensors are used to detect H 2 , NH 3 and H 2 S gases, which are biomarkers of such diseases as malabsorption, kidney failure and halitosis [ 43 , 44 , 45 ]. The high catalytic activity of phthalocyanine and porphyrin complexes can be attributed to the unsaturated low-coordination environment of central metal ions coordinated with four isoindole subunits [ 46 ]. Their catalytic activity in the process of NO oxidation is reflected in most cases by a negative shift of the oxidation voltammetric feature of NO by ca.…”
Section: Introductionmentioning
confidence: 99%